Respuestas
Respuesta dada por:
2
Bueno se procede de la siguiente manera
5x + 7 = 398 - 3x
5x + 3x = 398 - 7
8x = 391
x = 391/8
x = 48,875
Listo la respuesta es 48,875
5x + 7 = 398 - 3x
5x + 3x = 398 - 7
8x = 391
x = 391/8
x = 48,875
Listo la respuesta es 48,875
nicolsita123456789:
muy bien
Respuesta dada por:
1
¡Hola!.
Resolvemos.
![5x + 7 = 398 - 3x 5x + 7 = 398 - 3x](https://tex.z-dn.net/?f=5x+%2B+7+%3D+398+-+3x)
![5x + 3x = 398 - 7 5x + 3x = 398 - 7](https://tex.z-dn.net/?f=5x+%2B+3x+%3D+398+-+7)
![8x = 391 8x = 391](https://tex.z-dn.net/?f=8x+%3D+391)
![x = \frac{391}{8} x = \frac{391}{8}](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B391%7D%7B8%7D+)
Resolvemos.
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años